Structure and CO2 physisorption capacity of hydrotalcite-derived oxide. Issue 36 (February 2020) - Khalkhali, Mohammad; Zhu, Xuancan; Shi, Yixiang; Liu, Qingxia; Choi, Phillip; Zhang, Hao
Highlights: Obtain crystal and amorphous layered double oxides (LDOs) using molecular dynamics. Overall CO2 physisorption on amorphous LDO is higher than that on crystalline LDO. CO2 form stable adsorption layer near crystalline LDO, preventing further adsorption. CO2 shows ordered arrangement on crystalline LDO, but random on amorphous LDO. Abstract: Understanding the atomic structure and the corresponding adsorption mechanism of CO2 adsorbents is the key to develop efficient CO2 adsorption materials. Here, we studied hydrotalcite-derived oxides or layered double oxides (LDOs), one of the most promising candidates for the inexpensive and effective CO2 adsorption in the intermediate temperature regime, using atomistic simulation techniques. We first constructed the equilibrium structure of an LDO and showed that this oxide was crystalline with an MgO-like structure. In particular, Mg ions configured with the FCC arrangement of oxygen ions and most of the Al 3+ ions occupied octahedral positions by substituting Mg 2+ ions and the rest (∼10%) occupied the tetrahedral positions. We then compared the CO2 physisorption properties of the amorphous and crystalline LDOs that respectively represented LDOs form at lower and higher limits of hydrotalcite calcination. Static and dynamic adsorption analyses revealed that the amorphous LDO had overall higher physisorption capacity. CO2 molecules exhibited a random arrangement in the adsorption layer of the amorphous LDO but an ordered arrangement in the case of crystalline LDO. As a result, CO2 molecules were able to adsorb to and to desorb from the amorphous LDO surface dynamically while the stable adsorption layer near the crystalline LDO surface acted like a contamination preventing other CO2 molecules to adsorb, thereby lowering the overall adsorption capacity of the crystalline LDO. Depending on the level of crystallinity, the physisorption behavior of the mixed oxide forming during the hydrotalcite calcination is expected to change between two structures studied here.